2022
DOI: 10.1017/jfm.2022.603
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady motions in the turbulent separation bubble of a two-dimensional wing

Abstract: The unsteadiness of a turbulent separation bubble (TSB) formed close to the trailing edge of a two-dimensional wing was investigated using time-resolved particle image velocimetry. The angle of attack was set to 9.7° and the chord-based Reynolds number was 720 000. The TSB consisted of two shear layers and formed a triangular shape in the streamwise–wall-normal plane. The vertices of this triangle consisted of an intermittent detachment point, a fixed corner close to the airfoil trailing edge and an intermitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Figure 4 shows profiles of the normalized streamwise mean velocity (), root mean square of the streamwise velocity fluctuations () and the streamwise integral length scale () of the approach unperturbed TBL. Following Wang & Ghaemi (2022), the integral length scale was determined by integrating the autocorrelations of the streamwise velocity fluctuations () from the self-correlation point to the downstream location where , where is the exponential constant. For submerged cylinders, the section of the TBL that directly interacts with the cylinders has a stronger influence on the flow separation and wake dynamics around the cylinders (Lim, Castro & Hoxey 2007; Fang & Tachie 2019; Essel et al.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows profiles of the normalized streamwise mean velocity (), root mean square of the streamwise velocity fluctuations () and the streamwise integral length scale () of the approach unperturbed TBL. Following Wang & Ghaemi (2022), the integral length scale was determined by integrating the autocorrelations of the streamwise velocity fluctuations () from the self-correlation point to the downstream location where , where is the exponential constant. For submerged cylinders, the section of the TBL that directly interacts with the cylinders has a stronger influence on the flow separation and wake dynamics around the cylinders (Lim, Castro & Hoxey 2007; Fang & Tachie 2019; Essel et al.…”
Section: Resultsmentioning
confidence: 99%
“…These occurred because, compared with linear flapping, the lateral displacement velocity of arc flapping occurs in the direction of the X axis, as shown in Figure 2, thereby changing the velocity value of the equivalent incoming flow, as shown in Equation ( 8), and then causing a change in the attack angle, as shown in Equation ( 9) and Figure 4. It is known from the literature that a change in the attack angle will affect the strength of the leading-edge vortex of the hydrofoil [23,24]. Therefore, the different flapping modes had significant effects on the generation and evolution of the leading-edge vortices.…”
Section: Analysis Of the Influence Of Flapping Mode On The Structure ...mentioning
confidence: 99%
“…A. Andersen et al found, using the soap film technique, that the wake diagrams for pure heave and pure pitch motions are qualitatively similar [22]. Abbaspour and Song conducted research using three flapping modes-pure pitch, pure heave, and coupled heave-pitch-by means of experiments and numerical calculations, and concluded that an anti-Kármán vortex street always appears in the wake when employing coupled heave-pitch motion [23][24][25]. On this basis, Du et al further subdivided the flapping mode employing coupled heave-pitch motion, and compared the propulsion performance of the four resulting flapping modes, concluding that the greatest average thrust occurs when the maximum pitch angle is at the initial position and the pitch direction is the same as the heave direction, and no resistance is generated [26].…”
Section: Introductionmentioning
confidence: 99%